Evaluation of patients for tuberculosis prior to treatment with anti-tumor necrosis factor-α biological agents: Consensus meeting report March 2, 2002 / İstanbul - (:unkn) unknown (My University, 2002)
Tuberculosis (TB) remains a major health problem in Turkey. The annual incidence of TB is 30/100.000 according to the official reports, however, a figure of 40-50/100.000 may be more realistic due to the lack of regular reporting. It is estimated that about 30-50% of the adult population in Turkey have TB latent infection. Although it is difficult to determine the accurate prevalence as a consequence of BCG vaccination, the rate of PPD positivity in BCG-vaccinated adults over 18-year old in Turkey is 55% even when the cut-off value for positivity is taken as 15 mm, which suggests a high prevalence of the infection (1). Published reports revealed the increased prevalence of active TB disease in patients receiving immunosuppressive treatment for various conditions in Turkey. Three large retrospective studies showed that active TB was diagnosed in 4.2 % of renal transplant recipients, 1.8% in allogeneic stem cell transplant recipients and in 3.6% of patients with systemic lupus erythematosus (2-4). Most importantly, chemoprophylaxis for latent TB infection in immunosuppressive patients was found to be effective and safe in preventing active TB disease (2,3). Infliximab (Remicade) is a monoclonal antibody that inhibits the biologic activity of tumor necrosis factor alpha (TNFα). It is mainly used for the long-term treatment of rheumatoid arthritis (RA) and of Crohn's disease. Studies for new indications like ankylosing spondylitis and systemic vasculitis have been increasingly reported. Treatment with infliximab increases the risk of active TB infection. To date, a total of 117 cases have been reported and the annual incidence of active TB in USA rose from 6.8/100. 000 to 40/100.000 after the introduction of the infliximab therapy (5,6). Notably, the majority (80%) of reported cases are outside the USA, and the incidence of active TB outside the USA is thought to be 200/100.000. There was a high incidence (56%) of extrapulmonary disease and a vast majority (24%) of these cases were disseminated TB. This unusual clinical presentation has been attributed to the importance of TNFα in granuloma formation and decreased control of the infection in the absence of adequate TNFα activity (7).
Keywords: Anti-TNF therapy; Rheumatoid arthritis; Tuberculosis